Determinants of credit risk: Evidence from US national banks - Yuan, Yuequan (2019)
The present study explores the impact of macroeconomic and bank-specific determinants on the credit risk of 79 national banks in the US from 2011-2017. Using GMM estimations, this study finds that the real effective exchange rate and capital ratio are the primary determinants of credit risk. If there is an increase in the real effective exchange rate, the non-performing loans to total loans (NPLTL) ratio will decrease, whereas if a bank is more highly capitalized, NPLTL ratio is likely to be higher. Other variables, such as GDP growth rate, inflation, bank size, return on average assets, and loan loss provision to total loans did not exhibit any significant causal relationship with NPLTL ratio in this study. This study suggests that the Federal Government may direct its attention away from other macroeconomic indicators that would potentially depreciate the real effective exchange rate, because appreciation in the real effective exchange rate could enhance the capacity of those US borrowers who borrow money in foreign currency to repay their debts. It also suggests that the Federal Government may impose more prudent supervision of all national banks - to ensure they have a solid capital base to protect against any losses, while maintaining high credit standards.